Ability of noninvasive criteria to predict hemodynamically significant aortic obstruction in adults with coarctation of the aorta. (25th October 2016) - Astengo, Marco; Berntsson, Caroline; Johnsson, Åse A.; Eriksson, Peter; Dellborg, Mikael
Abstract: Objective: Coarctation of the aorta (CoA) is a common condition. Adult patients with newly diagnosed CoA and patients with recurring or residual CoA require evaluation of the severity of aortic obstruction. Cardiac catheterization is considered the gold standard for the evaluation of hemodynamically significant CoA. The European Society of Cardiology (ESC) Guidelines for the management of grown‐up congenital heart disease (GUCH) include noninvasive criteria for identifying significant CoA. Our aim was to investigate the ability of the Class I and Class IIa ESC recommendations to identify significant CoA at cardiac catheterization. Design: Sixty‐six adult patients with native or recurrent CoA underwent diagnostic cardiac catheterization at the GUCH unit at the Sahlgrenska University Hospital in Gothenburg from October 1998 to November 2013. Clinical and imaging data, as well as data about cardiac catheterization were retrospectively collected from patient records. Results: The Class I ESC recommendations predicted significant CoA with a sensitivity of 0.57, a specificity of 0.63, a positive predictive value of 0.67, and a negative predictive value of 0.53. The combination of Class I and Class IIa recommendations predicted significant CoA with a sensitivity of 0.75, a specificity of 0.42, a positive predictive value of 0.66 and a negative predictive value of 0.52. Conclusions: the noninvasive criteria proposed by the ESC guidelines to identify subjects with significant CoA performed poorly in our dataset. Further research is needed to develop more accurate, noninvasive criteria to evaluate CoA severity and thereby reduce the number of unnecessary cardiac catheterizations.